Insertion socioprofessionnelle de la jeunesse au Burkina Faso : de la politique réactive à une gouvernance territoriale - Taladi Narcisse YONLI (Revue Hybrides)
Public policies aimed at the social and professional integration of young people tend to view unemployment or the lack of jobs as a problem external to society. This often results in reactive, non-structural policies to counter this scourge. As a result, the employment needs of young people cannot be effectively met. It is therefore imperative to take structural action to adequately address the needs of young people. These needs are not necessarily those of politicians, but those in line with the real economic and territorial aspirations of young people. In other words, policies for the socio-professional integration of young people need to break away from a short-term approach and adopt a territorial one. The objective of this study is to contribute to an understanding of the employment problems faced by young people in Burkina Faso, notwithstanding the various policies in place. The study is based on documentary research supplemented by a qualitative survey through semi-structured interviews. The results of the fieldwork show that socio-professional integration is often thought outside the living environment or territory of young people. Thus, the territorial dimension (taking into account the social realities and needs of the areas considered) is the poor relation of public integration policies. Indeed, activities that the policymaker thinks are necessary for the development of youth are often promoted. The needs of the latter are thus established by proxy, modeled in an administrative straitjacket; this explains the failure or the mixed results of the projects or programs of professional insertion of the youth. This is why it is necessary to pay particular attention to the territorial needs of young people. To take into account the territorial dimension in terms of professional offers of the young people, is to register in the needs, the economic potentialities or characteristic aspirations of the social structures or environment of life of the young people. There cannot be a single undifferentiated national policy for the socio-professional integration of young people, but rather public policies that are territorialized. This is the guarantee of a sustainable integration policy.